The First Cycle of Study: Teaching and Learning at Cross Purposes? - Fillion, Réal (Canadian Journal of Higher Education, 2015)
The contemporary university has grown to be a fairly complex institution sustained by many competing interests, not all of which are directly concerned with promoting the work of study, broadly conceived. My concern in the following is with the quality of the subjective experience of studying that universities are still meant to provide. By subjective experience I mean the mindful engagement that is study, and my focus is on such study as it is found in undergraduate programs leading to undergraduate degrees. Given the threat of a growing indifference between professors and students concerning their shared engagement in courses offered at the undergraduate level (offered because of professors’ institutional obligations, taken because of students’ degree requirements), I reconsider the subjective investment of mindful engagement that these courses nevertheless represent.